Lactate Dehydrogenase A Depletion Alters MyC-CaP Tumor Metabolism, Microenvironment, and CAR T Cell Therapy - Mayuresh M. Mane; Ivan J. Cohen; Ellen Ackerstaff; Khalid Shalaby; Jenny N. Ijoma; Myat Ko; Masatomo Maeda; Avi S. Albeg; Kiranmayi Vemuri; Jaya Satagopan; Anna Moroz; Juan Zurita; et al. (Molecular Therapy: Oncolytics, 2020)
To enhance human prostate-specific membrane antigen (hPSMA)-specific chimeric antigen receptor (CAR) T cell therapy in a hPSMA+ MyC-CaP tumor model, we studied and imaged the effect of lactate dehydrogenase A (LDH-A) depletion on the tumor microenvironment (TME) and tumor progression. Effective LDH-A short hairpin RNA (shRNA) knockdown (KD) was achieved in MyC-CaP:hPSMA+ Renilla luciferase (RLuc)-internal ribosome entry site (IRES)-GFP tumor cells, and changes in tumor cell metabolism and in the TME were monitored. LDH-A downregulation significantly inhibited cell proliferation and subcutaneous tumor growth compared to control cells and tumors. However, total tumor lactate concentration did not differ significantly between LDH-A knockdown and control tumors, reflecting the lower vascularity, blood flow, and clearance of lactate from LDH-A knockdown tumors. Comparing treatment responses of MyC-CaP tumors with LDH-A depletion and/or anti-hPSMA CAR T cells showed that the dominant effect on tumor growth was LDH-A depletion. With anti-hPSMA CAR T cell treatment, tumor growth was significantly slower when combined with tumor LDH-A depletion and compared to control tumor growth (p < 0.0001). The lack of a complete tumor response in our animal model can be explained in part by (1) the lower activity of human CAR T cells against hPSMA-expressing murine tumors in a murine host, and (2) a loss of hPSMA antigen from the tumor cell surface in progressive generations of tumor cells.